2012
DOI: 10.1021/cm3008864
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-Dependent Pathways of Poly-3-hexylthiophene Photo-Oxidation

Abstract: The photodegradation kinetics of regioregular poly-3-hexylthiophene (P3HT) thin films (∼150 nm) upon illumination with both visible light of 525 nm and UV light of 365 nm has been studied using UV/vis and FTIR spectroscopy in order to probe both the disruption of the π-conjugated system and the chemical product evolution. Reaction effectiveness and product evolution turn out to depend strongly on the wavelength of the incident light. Under UV light, the π-conjugated system and the hexyl side chain are degraded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 20 publications
7
69
0
Order By: Relevance
“…Restricting our discussion to those mechanisms, it is generally accepted that UV radiation is able to promote physical or chemical degradation in polymeric materials, as this energy could be enough to break chemical bonds [37][38][39]. Although the threshold photon energy to break chemical bonds could differ for different polymers, as a general rule deeper degradation from UV photons might be expected, in agreement to our results.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Restricting our discussion to those mechanisms, it is generally accepted that UV radiation is able to promote physical or chemical degradation in polymeric materials, as this energy could be enough to break chemical bonds [37][38][39]. Although the threshold photon energy to break chemical bonds could differ for different polymers, as a general rule deeper degradation from UV photons might be expected, in agreement to our results.…”
Section: Resultssupporting
confidence: 88%
“…Although the threshold photon energy to break chemical bonds could differ for different polymers, as a general rule deeper degradation from UV photons might be expected, in agreement to our results. Hintz et al [39] reported the photodegradation of P3HT upon illumination with both visible (525 nm) and UV (365 nm) light, finding that the degradation products depend strongly on the wavelength of the incident light. For UV irradiation the π-conjugated system and the hexyl side chain are degraded simultaneously, while for visible light only the π-conjugated system is affected.…”
Section: Resultsmentioning
confidence: 99%
“…7,8,16,[20][21][22] In these polymers, the photo-oxidation process seems to follow a radical chain based mechanism, which probably starts on the α-carbon atoms of the alkyl chains. 8,21 The addition of PCBM to films of these polymers results in decreased degradation rates, probably due to the radical scavenging effect of the fullerene.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10,12,13,16,19] The assignment of the different vibrational modes has been done by a direct comparison with the spectra of pure PC 70 BM and Si-PCPDTBT:PC 70 BM. (Fig.…”
Section: Bulk Investigationmentioning
confidence: 99%